2009
DOI: 10.1177/1086026609333419
|View full text |Cite
|
Sign up to set email alerts
|

From “Politico-Scientists” to Democratizing Science Movements

Abstract: The Committee for Nuclear Information (CNI) was one of the first movements to translate expert knowledge to the public. It was led by “politico-scientists” who meant to advance an ethics of science by contributing to public understanding. Since then, citizens have taken research into their own hands, using it to frame issues, challenge corporate practices, and change policy. Movement methods that respond to consistent activist concerns about science are reflected in “democratizing science movements” (DSMs) tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 34 publications
(30 reference statements)
0
10
0
Order By: Relevance
“…This exploratory case study focused on examining how Flint Water Study scientists utilized Twitter as a communication and mobilization channel to raise awareness about the lead contamination of Flint water before the national news media reported on the issue as a national-level crisis. Previous studies on activism and politico-scientists have suggested the unique role scientists played in presenting social issues with research and facts in a manner that is approachable and understandable to laypersons (Frickel, 2004a;Lubitow, 2013;McCormick, 2009). Findings from a content analysis indicate Twitter was primarily used to educate the public about the scientific facts and research related to lead contamination in Flint water.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…This exploratory case study focused on examining how Flint Water Study scientists utilized Twitter as a communication and mobilization channel to raise awareness about the lead contamination of Flint water before the national news media reported on the issue as a national-level crisis. Previous studies on activism and politico-scientists have suggested the unique role scientists played in presenting social issues with research and facts in a manner that is approachable and understandable to laypersons (Frickel, 2004a;Lubitow, 2013;McCormick, 2009). Findings from a content analysis indicate Twitter was primarily used to educate the public about the scientific facts and research related to lead contamination in Flint water.…”
Section: Discussionmentioning
confidence: 99%
“…Social movement scholars have examined the ways scientists have collaborated with traditional activists to advance social change efforts in the public arena (Brown, 1992;Edge & Eyles, 2015;Frickel, 2004a;Lubitow, 2013) for a range of issues such as regulating bisphenol-A (Lubitow, 2013) and genetic toxicology (Frickel, 2004a) and preventing climate change (McCormick, 2009). These studies examined the mobilization of scientific experts and how scientists have been integrated into social activists' movements.…”
Section: Role Of Science In Activism: Understanding Politico-scientistsmentioning
confidence: 99%
See 2 more Smart Citations
“…The microblogging service Twitter is one of these means for public engagement and is used by numerous academics from all disciplines (Ke et al, 2017). Twitter is used in the context of certain crises, when scientists turn into activists (Jangh and Lee, 2018; McCormick, 2009). But it is also used in the day-to-day communication of scholars, who can thus actively engage with diverse publics and influence their perceptions of science (Dudo and Besley, 2016).…”
Section: Introductionmentioning
confidence: 99%